1992
DOI: 10.1590/s0102-311x1992000300007
|View full text |Cite
|
Sign up to set email alerts
|

Problems of health insurance coverage and health care in the United States: public and private solution strategies

Abstract: A nearly universal consensus has developed in the United States that the current health care financing system is a failure. The system has been unable to control the continuing rapid rise in health care costs (by far, the highest in the world), and it has been unable to stem the growing population that has no health insurance coverage (at least 36 million people). There is nearly universal political agreement that government must provide health insurance to a far greater share of the population than ever befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Sarker, Sultana, Ahmed, Mahumud, Morton, & Khan (2018) concluded with the results on creation and development of community-based health care services packages that are in line with Bangladesh's health care funding policy and the World Health for developing social health insurance as part of Universal Health Coverage. Brown (1992) concluded that there is a universal political consensus that the government must provide a far greater proportion of the population with health care than ever before. Obermann, Jowett, O Alcantara, Banzon, & Bodart's (2006) research was concluded on the fact that SHI has so far been a success story in the Philippines and provides lessons for countries in the same common situation.…”
Section: Satisfaction Level and Government Health Insurance Programmentioning
confidence: 99%
“…Sarker, Sultana, Ahmed, Mahumud, Morton, & Khan (2018) concluded with the results on creation and development of community-based health care services packages that are in line with Bangladesh's health care funding policy and the World Health for developing social health insurance as part of Universal Health Coverage. Brown (1992) concluded that there is a universal political consensus that the government must provide a far greater proportion of the population with health care than ever before. Obermann, Jowett, O Alcantara, Banzon, & Bodart's (2006) research was concluded on the fact that SHI has so far been a success story in the Philippines and provides lessons for countries in the same common situation.…”
Section: Satisfaction Level and Government Health Insurance Programmentioning
confidence: 99%